Socioeconomic and environmental factors associated with waterpipe tobacco smoking among Iranian adults: a PERSIAN cohort-based cross-sectional study - Telma Zahirian Moghadam; Hamed Zandian; Mehdi Fazlzadeh; Mohammad Ebrahimi Kalan; Farhad Pourfarzi (BMC, 2023)
Abstract Background Waterpipe tobacco smoking (WTS) is associated with several deleterious health outcomes. We sought to estimate the prevalence of WTS and explore socioeconomic inequalities associated with this culturally-rooted tobacco smoking practice among Iranian adults. Methods A cross-sectional analysis was conducted among 20,460 adults (ages 18 and older) enrolled in the PERSIAN cohort study during 2020. Data were collected on socioeconomic status (SES), lifestyle, alcohol consumption, cigarette smoking, and several risk factors related to non-communicable diseases. The concentration curve and relative concentration index (RCI) were administered to assess and quantify the SES-based inequality in WTS. Results Overall age-adjusted prevalence of past-month WTS was 5.1% (95%CI:4.6-5.8), with about 1% for women and 10.6 for men. Age-adjusted prevalence of WTS was higher among younger adults, men, cigarette smokers, obese adults, and those with higher SES. The RCI estimation showed that WTS is more popular among adults with high income and education. WTS was higher among younger adults, cigarette smokers, obese adults, and those with higher SES. Conclusion There is a clear socioeconomic inequality in WTS, with a higher prevalence among adults with higher income and education. The findings suggest the need for targeted interventions to address this inequality and reduce the prevalence of WTS among high-income communities.